A Qualitative Study Exploring the Experiences of Tuberculosis Patients Who Have Successfully Recovered - Cri Sajjana Prajna Wekadigunawan; Dhini Yumaniar; Farah Shabrina (Journal of Epidemiology and Public Health, 2023)
Background: Tuberculosis cases in Indonesia occupy the second highest position after India. TB eradication is an important program in the SDGs 2030. Recovering from Tuberculosis is a blessing. This study aimed to explore the experiences of tuberculosis sufferers who have recovered. Subjects and Method: This qualitative study was conducted in the Yosodadi Community from January to February 2023. A total of 12 patients with tuberculosis who had successfully recovered were selected for this study. The variable of this study was the experiences of tuberculosis patients who have successfully recovered. A depth interview was used to obtain the data. The data were analyzed descriptively. Results: The study showed the importance of patients knowing their disease, the support of those around them, and health workers who have good empathy towards TB patients. This research also found the importance of health providers and patient families being asked to pay attention to the mental health problems suffered by TB patients. Conclusion: Vaccine reluctance is a huge problem in the face of a pandemic that is not yet over. Even with to achieve recovery for TB patients, efforts are needed to understand the mental condition of TB patients. Policymakers must consider ongoing health education regarding TB patient assistance by family and health workers. Keywords: Empathy, family support, health provider, mental health, patient, tuberculosis. Correspondence:Cri Sajjana Prajna Wekadigunawan. Faculty of Health Sciences Esa Unggul University. Jl Terusan Arjuna, Jakarta Barat. Email: weka.gunawan@esaunggul.ac.id. Mobile: +6281299264727.